Optimal Number of Needle Punctures in EUS-FNA/B with ROSE for Solid Pancreatic Lesions - Naomi Uchiyama; Hiroshi Kawakami; Yoshinori Ozono; Hiroshi Hatada; Soichiro Ogawa; Satoshi Sekiguchi; Hiroshi Noguchi; Yuichiro Sato (Diagnostics)
Background and Objectives: Endoscopic ultrasonography (EUS)-guided fine-needle aspiration/biopsy (FNA/B) is widely used for solid pancreatic lesions; however, the optimal number of needle punctures required to achieve high diagnostic accuracy remains unclear. This study aimed to identify the ideal number of punctures required for solid pancreatic lesions using EUS-FNA/B. Methods: This single-center retrospective study included 598 patients who underwent EUS-FNA/B for solid pancreatic lesions. We analyzed the cumulative tissue acquisition rates and diagnostic accuracy rates for cytology and histology, and identified the factors associated with diagnostic accuracy using univariate and multivariate analyses. Rapid on-site cytological evaluation was performed in all cases. Results: Cumulative tissue acquisition rates were 95.6% and 92.5% for cytology and histology, respectively. The diagnostic accuracy for cytology increased from 72.6% in the first puncture to 78.8% in the second puncture (p = 0.0233). In contrast, the diagnostic accuracy of histology increased from 72.0% at the first puncture to 83.2% at the third puncture (p = 0.0412). Statistically significant differences were noted between the first and second punctures for cytology, and between the first, second, and third punctures for histology. Univariate and multivariate analyses were conducted to identify factors associated with diagnostic accuracy. In cytology, sex was identified as a significant contributing factor, whereas no independent predictors were found in histology. Conclusions: These findings suggest that two-needle punctures are optimal for cytology, and three-needle punctures are optimal for the histological diagnosis of solid pancreatic lesions using EUS-FNA/B.